Three-dimensional spatio-temporal modelling of store operated Ca2+ entry: insights into ER refilling and the spatial signature of Ca2+ signals - McIvor, Emma; Coombes, Stephen; Thul, Ruediger (Elsevier, 2018)
The spatial organisation of Orai channels and SERCA pumps within ER-PM junctions is important for enhancing the versatility and specificity of subcellular Ca2+ signals generated during store operated Ca2+ entry (SOCE). In this paper we present a novel three dimensional spatio-temporal model describing Ca2+ dynamics in the ER-PM junction and sub-PM ER during SOCE. We investigate the role of Orai channel and SERCA pump location to provide insights into how these components shape the Ca2+ signals generated and affect ER refilling. We find that the organisation of Orai channels within the ER-PM junction controls the amplitude and shape of the Ca2+ profile but does not enhance ER refilling. The model shows that ER refilling is only weakly affected by the location of SERCA2b pumps within the ER-PM junction and that the placement of SERCA2a pumps within the ER-PM junction has much greater control over ER refilling.